Cognitive therapy techniques : a practitioner's guide - Leahy, Robert L. (New York : The Guilford Press, 2017)
"This indispensable book has given many tens of thousands of practitioners a wealth of evidence-based tools for maximizing the power of cognitive therapy and tailoring it to individual clients. Leading authority Robert L. Leahy describes ways to help clients identify and modify problematic thoughts, core beliefs, and patterns of worry, self-criticism, and approval-seeking; evaluate personal schemas; cope with painful emotions; and take action to achieve their goals. Each technique includes vivid case examples and sample dialogues. Featuring 125 reproducible forms, the print book has a large-size format for easy photocopying; purchasers also get access to a Web page where they can download and print the reproducible materials. New to This Edition *Numerous additional techniques and reproducible tools, including 48 new or revised forms. *Chapters on decision-making problems, intrusive thoughts, and anger management issues. *Incorporates the latest theory and research as well as cutting-edge techniques drawn from acceptance and commitment therapy (ACT), behavioral activation, dialectical behavior therapy (DBT), emotional schema therapy, and the metacognitive model. *Significantly revised chapters on emotion regulation and worries. *Filled-out examples for many of the forms"--
"Subject Areas/Keywords: anger, approval seeking, assumptions, avoidance, basics, CBT, challenging, clinical practice, cognitive distortions, cognitive therapy, cognitive-behavioral therapy, CT, decision making, distortion, eliciting, emotion regulation, emotional processing, emotions, evaluating, examining, forms, homework, interventions, intrusive, logical errors, modifying, practitioners, psychotherapists, psychotherapy, schemas, self-criticism, skills, strategies, techniques, testing, therapists, thoughts, training DESCRIPTION This indispensable book has given many tens of thousands of practitioners a wealth of evidence-based tools for maximizing the power of cognitive therapy and tailoring it to individual clients. Leading authority Robert L. Leahy describes ways to help clients identify and modify problematic thoughts, core beliefs, and patterns of worry, self-criticism, and approval-seeking; evaluate personal schemas; cope with painful emotions; and take action to achieve their goals. Each technique includes vivid case examples and sample dialogues. Featuring 125 reproducible forms, the print book has a large-size format for easy photocopying; purchasers also get access to a Web page where they can download and print the reproducible materials. "--
Machine generated contents note: I. Beginning Cognitive Therapy -- 1. Introduction -- II. Techniques -- 2. Eliciting Thoughts -- 3. Evaluating and Testing Thoughts -- 4. Evaluating Assumptions and Rules -- 5. Examining Information-Processing and Logical Errors -- 6. Modifying Decision Making -- 7. Responding to and Evaluating Intrusive Thoughts -- 8. Modifying Worry and Rumination -- 9. Putting Things in Perspective -- 10. Identifying and Modifying Schemas -- 11. Emotion Regulation Techniques -- III. Specific Applications -- 12. Examining and Challenging Cognitive Distortions -- 13. Modifying Need for Approval -- 14. Challenging Self-Criticism -- 15. Managing Anger -- 16. Concluding Comments -- References -- Index.
Includes bibliographical references (pages 501-507) and index.
Keywords: Cognitive therapy; MEDICAL / Psychiatry / General; SOCIAL SCIENCE / Social Work; PSYCHOLOGY / Clinical Psychology